PENGEMBANGAN MEDIA INTERAKTIF WIZER.ME BERBASIS ETNOMATEMATIKA RUMAH PANGGUNG KAJANG LAKO PADA MATERI BANGUN DATAR UNTUK PESERTA DIDIK KELAS III SEKOLAH DASAR - Desita Novi; Eka Sastrawati; Hendra Budiono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop interactive learning media using Wizer.me based on the ethnomathematics of the Kajang Lako traditional stilt house for teaching plane shapes to third-grade elementary school students, determine the validity level of the developed media, and assess its practicality in classroom use. The research employed the Research and Development (R&D) method with the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The data collected included qualitative data from comments and suggestions provided by experts, teachers, and students, as well as quantitative data obtained through validation questionnaires completed by material experts, media experts, language experts, and practicality questionnaires from teachers and students. The study was conducted at SDN 3/IV Kota Jambi. The resulting product is an interactive digital learning media created with Wizer.me and integrated with cultural elements of the Kajang Lako traditional house as contextual visual representations of plane shapes. The validation results show that the media achieved scores categorized as valid and highly valid, with average scores of 4.20 from the material expert, 5.00 from the media expert, and 4.80 from the language expert. The practicality assessment obtained a score of 4.90 from teachers, 4.90 from the small-group trial, and 4.81 from the large-group trial, all classified as very practical. Based on these findings, the interactive Wizer.me learning media based on the ethnomathematics of the Kajang Lako traditional house is considered highly valid, highly practical, and suitable for use as a learning media for plane shapes in third-grade elementary school.